Evaluación y comparación de un diseño de un sistema de alcantarillado pluvial convencional y un sistema de drenaje mediante tecnología SUDS, para el sector de Mochuelo Bajo en la localidad de ciudad Bolívar en Bogotá D.C. - Bucheli Campo, Laura Rocio; Rodriguez Romero, Ana Gabriela (Ingeniería, 2022)
Con el presente estudio, se busca dar solución a la problemática de manejo de aguas lluvias en el sector de mochuelo bajo, el cual actualmente genera inundaciones y represamientos de aguas tanto pluviales como residuales en diferentes sectores de la zona, diseñando un sistema de alcantarillado pluvial convencional y un sistema donde se implementen SUDS. Con base a los diseños realizados, se realizó una comparación técnica, económica, ambiental y operativa de los sistemas con el fin de identificar cual es más adecuado para la zona de estudio, teniendo en cuenta que ambos diseños dan solución a la problemática. Los resultados demostraron que la implementación de tipologías SUDS son técnica, ambiental y socialmente más efectivas que la implementación de un alcantarillado netamente convencional, sin embargo, la implementación de estos está limitado a disponibilidad de áreas, urbanismo y recursos económicos, por lo que, para el caso específico de estudio, donde el desarrollo urbano se ha llevado a cabo de manera informal y no se cuenta con un urbanismo adecuado, esta no es la opción más eficiente. La implementación de SUDS implica una evaluación de condiciones iniciales específicas para su uso, por lo que, en condiciones de desarrollo urbano ideales, es recomendable evaluar la aplicabilidad de este tipo de sistemas, ya que ofrece beneficios importantes en factores ambientales y sociales.

Due to the exponential growth of cities and the increase of non-permeable hard areas and runoff volumes, accompanied by climate change, it is important to implement systems that mitigate the problems associated with the poor performance of conventional storm sewers when extreme events occur. This leads to the implementation of non-conventional alternative systems that, through nature-based solutions, mitigate and delay storm peaks, thus avoiding the collapse of sewerage networks. Similarly, it has been proven in other implementation cases that the application of Sustainable Urban Drainage Systems not only leads to a technical benefit, but also, since most of them are accompanied by the implementation of green areas and urban renewal, there is an improvement in the conductivity of fauna species, an increase in vegetation cover and an improvement in the quality of life of the benefited population. The sector of Mochuelo Bajo in the locality of Ciudad Bolivar, in the city of Bogota, is taken as a case study, based on the Consulting Contract No. Uaesp-752-2020, whose purpose is "Preparation of detailed studies and designs to complete 100% of the sanitary and storm sewerage networks of Mochuelo Alto and Mochuelo Bajo and the optimization of the wastewater plant of both sectors, in the locality of Ciudad Bolivar". This study seeks to solve the problem of rainwater management in the sector of Mochuelo Bajo, which currently generates flooding and damming of both rainwater and wastewater in different sectors of the area, designing a conventional storm sewer system and a system where SUDS are implemented. Based on the designs, a technical, economic, environmental and operational comparison of the systems was made in order to identify which one is more adequate for the study area, taking into account that both designs provide a solution to the problem. The results showed that the implementation of SUDS typologies are technically, environmentally and socially more effective than the implementation of a purely conventional sewerage system; however, their implementation is limited to the availability of areas, urban planning and economic resources, so that, for the specific case of study, where urban development has been carried out informally and there is no adequate urban planning, this is not the most efficient option. The implementation of SUDS implies an evaluation of specific initial conditions for their use, so that, under ideal urban development conditions, it is advisable to evaluate the applicability of this type of system, since it offers important benefits in environmental and social factors
Evaluation and comparison of a design of a conventional storm sewer system and a drainage system using SUDS technology for the sector of Mochuelo Bajo in the district of Ciudad Bolívar in Bogotá D.C.
Keywords: Alcantarillado -- Mochuelo Bajo - Localidad de Ciudad Bolívar, Bogotá; Tratamiento de aguas residuales -- Mochuelo Bajo - Localidad de Ciudad Bolívar, Bogotá; Alcantarillas -- Diseño y Construcción -- Mochuelo Bajo - Localidad de Ciudad Bolívar, Bogotá; Alcantarillado -- Mochuelo Bajo - Localidad de Ciudad Bolívar, Bogotá; Sewerage -- Mochuelo Bajo - City of Ciudad Bolívar, Bogotá; Tratamiento de aguas residuales -- Mochuelo Bajo - Localidad de Ciudad Bolívar, Bogotá; Wastewater treatment -- Mochuelo Bajo - City of Ciudad Bolívar, Bogotá; Alcantarillas -- Diseño y Construcción -- Mochuelo Bajo - Localidad de Ciudad Bolívar, Bogotá; Sewers -- Design and Construction -- Mochuelo Bajo - City of Ciudad Bolívar, Bogotá